Analisa Pemanfaatan Limbah Plastik Sebagai Bahan Baku Pembuatan Paving Block - Khaq, Nur Arinal; Damara, Bobby (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Plastic waste is most commonly found around us and is a source of pollution in the environment, both on land and in water. paving is formed into a rectangle with a press made manually. This paving can be used as a path in the plantation or at home because it is made from recycled waste that pollutes the environment. Methods used Experimental method. The optimum compressive strength value is obtained in sample 2 of LDPE plastic type and decreases in sample 1 of PET type The decrease in compressive strength value occurs because PET plastic type dries quickly. The optimum compressive strength value in LDPE plastic type of 3.341 MPa can also be caused because it is easy to fuse when heated and dries long so that it can be molded easily. The compressive strength value in the 33% variation decreased because the plastic shreds overlapped with other plastic shreds, reducing its compressive strength. The type of waste plastic pet compressive strength produced is smaller than other types and dries easily so it is difficult to mold, the average weight of 1.089 gr / cm3 is heavier than other types of plastic, for specific gravity in water heavier mixed variation 33% with an average of 0.266 gr / cm3 and for the smallest weight type HDPE with an average of 0, 181 gr/cm3, For all types of testing does not meet the minimum requirements of SNI 03-0691-1996 as a paving block with quality D with the required average compressive strength of 10 Mpa and a minimum compressive strength of 8.5 Mpa, in this test the highest compressive strength is in the type of LDPE sample 2 of 3.341 Mpa and for the lowest in the type of PET sample 1 of 0.248 Mpa.